Fugue States: Modiano Romancier - Lynn A. Higgins (Studies in 20th & 21st Century Literature, 2007)
The essay shows how in Dora Bruder, Modiano is able to call upon imagination and mobilize the novelist's craft while remaining faithful to historical truth.
Keywords: Dora Bruder; Modiano; imagination; Modiano Romancier